2017
DOI: 10.1051/matecconf/201711203009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of build orientation on the mechanical properties of medical implants made from PA 2200 by Selective Laser Sintering

Abstract: Abstract. This paper presents a series of research that have been made by the authors in the field of medical implants realized from PA 2200 powder material using the Selective Laser Sintering (SLS) method. Several sets of samples differently oriented into the working area of the machine were manufactured from PA 2200 by SLS, in order to determine which is the recommended orientation to be used during the manufacturing process, in such a way that at the end the mechanical properties (e.g. Compressive strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The study revealed that the material was transversely isotropic in Young’s modulus, strained to failure and generally orthotropic in ultimate tensile strength as well as inhomogeneous throughout the build volume; these results further emphasized the findings of Ajoku et al (2006) and Caulfield et al (2007). Also, Razvan et al (2017) have investigated the effects of build orientation on the compressive strength of SLS parts manufactured from PA2200 combatable material to determine the optimal orientation at which the mechanical properties of fabricated parts are close to those of the human bones. The samples were manufactured at LP of 4 – 4.5W and different build orientations.…”
Section: Introductionmentioning
confidence: 73%
“…The study revealed that the material was transversely isotropic in Young’s modulus, strained to failure and generally orthotropic in ultimate tensile strength as well as inhomogeneous throughout the build volume; these results further emphasized the findings of Ajoku et al (2006) and Caulfield et al (2007). Also, Razvan et al (2017) have investigated the effects of build orientation on the compressive strength of SLS parts manufactured from PA2200 combatable material to determine the optimal orientation at which the mechanical properties of fabricated parts are close to those of the human bones. The samples were manufactured at LP of 4 – 4.5W and different build orientations.…”
Section: Introductionmentioning
confidence: 73%
“…Better mechanical properties are achieved along with the printing layer and worse in a direction normal to the printing layer. There are many ways in which the mechanical properties of materials can be tested [26][27][28]. Also, greater precision and greater detailed geometry can be achieved in planes parallel to the print layer where print accuracy is higher.…”
Section: Additive Manufacturing Technologiesmentioning
confidence: 99%